Photoluminescence properties of Ce3+/Mn2+ doped calcium zirconium silicate phosphors with energy transfer for white LEDs. Issue 15 (15th November 2016) - Wang, Fei; Wang, Wanrong; Jin, Ye
Abstract: A series of Ce 3+ doped and Ce 3+ /Mn 2+ co-doped calcium zirconium silicate CaZrSi2 O7 (CZS) phosphors have been synthesized via conventional high temperature solid state reactions. The luminescence properties, energy transfer between Ce 3+ and Mn 2+ have been investigated systematically. Under 320 nm excitation, the phosphor CZS: 0.05Ce 3+ exhibit strong blue emission ranging from 330 nm to 500 nm, attributed to the spin-allowed 5d-4f transitions of Ce 3+ ions. There are two different emission centers of Ce 3+ ions, Ce 3+ (I) and Ce 3+ (II). The emission spectra of Ce 3+, Mn 2+ co-doped phosphors shows a broad emission around 550 nm corresponding to the 4 T1 ( 4 G)- 6 A1 ( 6 S) spin-forbidden transition of Mn 2+ . The energy transfer between Ce 3+ and Mn 2+ is detected and the transfer efficiency of Ce 3+ (II) to Mn 2+ is faster than that of Ce 3+ (I) to Mn 2+ . The resonant type is identified via dipole-dipole mechanism. Additionally, a blue-shift emission of Ce 3+ and a red-shift emission of Mn 2+ have been observed following the increase of Mn 2+ content in relation to the energy transfer. Thermal quenching has been investigated and the emission spectra show a blue-shift with the temperature increases, which have been discussed in details. CZS: 0.05Ce 3+, yMn 2+ phosphors can be tuned from blue to white and even to yellow by adjusting the Mn 2+ content. All the results indicate that CZS: Ce 3+, Mn 2+ phosphor have a potential application for near-UV LEDs.